The language myth : why language is not an instinct - Evans, Vyvyan (Cambridge : Cambridge University Press, 2014)
Language is central to our lives, the cultural tool that arguably sets us apart from other species. Some scientists have argued that language is innate, a type of unique human'instinct' pre-programmed in us from birth. In this book, Vyvyan Evans argues that this received wisdom is, in fact, a myth. Debunking the notion of a language'instinct', Evans demonstrates that language is related to other animal forms of communication; that languages exhibit staggering diversity; that we learn our mother tongue drawing on general properties and abilities of the human mind, rather than an inborn'universal' grammar; that language is not autonomous but is closely related to other aspects of our mental lives; and that, ultimately, language and the mind reflect and draw upon the way we interact with others in the world. Compellingly written and drawing on cutting-edge research, The Language Myth sets out a forceful alternative to the received wisdom, showing how language and the mind really work.
Machine generated contents note: Acknowledgements; 1. Language and mind rethought; 2. Is human language unrelated to animal communication systems?; 3. Are there language universals?; 4. Is language innate?; 5. Is language a distinct module in the mind?; 6. Is there a universal Mentalese?; 7. Is thought independent of language?; 8. Language and mind regained.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Linguistic universals; Cognitive grammar; Innateness hypothesis (Linguistics); Language and languages -- Philosophy; Psycholinguistics